Nerlovian stock adjustment approach to electric power consumption among households’ in Nigeria - Bashir, Najeem O.; Kadiri, Abu; Bisiriyu, Isiaka B. (Energy Economics Letters, 2025)
The research examined the impact of time on households’ current electricity demand among households in Nigeria. Specifically it examined the effects of consumers’ previously earned income and acquired electrical appliances on their current energy consumption, hence a dynamic demand analysis. The study analyzed 42 years annual series spanning 1981 through 2023. Household Income, Electricity demand and tariff are the study variables. An ARDL regression and other robustness checks were fitted. Results showed that previous Electricity demand caused current demand to significantly rise by 37%. Increase in households’ past and current income also led to an increase in current power demand. About 91.8% of the short and long run imbalances among the series are corrected in subsequent years, as indicated by the estimated ECT(-1). It is concluded that past electricity demand and previous income positively and significantly influenced households’ current power demand, albeit the dampening effect of power tariff. As tariff-increase polices are been implemented, regular income review is recommended. If tariff increase was necessary, it should be mildly administered given its dampening effect on real income.